In vitro changes in secretion activity of rat ovarian fragments induced by molybdenum - Roychoudhury, Shubhadeep; Detvanová, Lenka; Sirotkin, Alexander V; Toman, R; Kolesárová, Adriana (Physiological research, 2014)
The aim of this in vitro study was to examine the secretion activity (progesterone, 17beta-estradiol and insulin-like growth factor-I) of rat ovarian fragments after molybdenum (Mo) addition. Rat ovarian fragments were incubated with ammonium molybdate (NH(4))(6)Mo(7)O(24).4H(2)O at the doses 90, 170, 330 and 500 microg.ml(-1) for 24 h and compared with control group without Mo addition. Release of progesterone (P(4)), estradiol (17beta-estradiol) and insulin-like growth factor I (IGF-I) by ovarian fragments was assessed by radioimmunoassay (RIA). Data show that P(4) release by ovarian fragments was not affected by (NH(4))(6).Mo(7)O(24).4H(2)O addition at all the doses used (90-500 microg.ml(-1)). However, addition of ammonium molybdate was found to cause a significant (P<0.05) dose-dependent decrease (at the doses 90, 170 and 500 microg.ml(-1)) in release of 17beta-estradiol by ovarian fragments in comparison to control. Also, addition of ammonium molybdate significantly (P<0.05) inhibited IGF-I release at all the doses (90-500 microg.ml(-1)) used in the study. Results suggest ammonium molybdate induced inhibition in the release of growth factor IGF-I and its dose-dependent effect on secretion of steroid hormone 17beta-estradiol but not progesterone. These data contribute to new insights regarding the mechanism of action of Mo on rat ovarian functions.
Keywords: techniky in vitro; insulinu podobný růstový faktor I; zvířata; Rats; molybden; ovarium; Ovary; progesteron; Estradiol; krysa rodu Rattus; ženské pohlaví; Dose-Response Relationship, Drug; Animals; vztah mezi dávkou a účinkem léčiva; estradiol; Progesterone; Insulin-Like Growth Factor I; In Vitro Techniques; Molybdenum; Female